Bipolar cell

CN122843387APending Publication Date: 2026-09-29TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511999610.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-03-25
Filing Date
2025-12-29
Publication Date
2026-09-29

AI Technical Summary

Benefits of technology

[0013]根据本发明,能够提供一种即使使用硅系负极活性物质也能够抑制负极活性物质层在充电时发生膨胀时的集电体的破损,并且能够抑制正极与负极的短路的双极型电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122843387A_ABST
    Figure CN122843387A_ABST
Patent Text Reader

Abstract

This invention provides a bipolar battery capable of suppressing short circuits between the positive and negative electrodes. The bipolar battery of this invention comprises bipolar electrode sheets and a non-aqueous electrolyte. The bipolar electrode sheets have: a negative current collector, on which a second metal foil having one or more through holes is laminated via an adhesive layer comprising a thermoplastic resin on the surface of a first metal foil without through holes; a negative active material layer formed on the surface of the second metal foil and comprising a silicon-based negative active material; a positive current collector laminated on the back side of the first metal foil; and a positive active material layer formed on the back side of the positive current collector. The adhesive layer comprises: a first adhesive portion existing between the surface of the first metal foil and the back side of the second metal foil; and a second adhesive portion existing within one or more through holes of the second metal foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a bipolar battery. Background Technology

[0002] As a type of non-aqueous electrolyte secondary battery such as lithium-ion secondary batteries, a bipolar battery is known, which includes a bipolar electrode sheet in which a negative electrode active material layer is formed on one side of the current collector and a positive electrode active material layer is formed on the other side of the current collector.

[0003] Bipolar batteries can increase capacity per unit volume. To further increase the capacity of bipolar batteries, the inventors investigated the introduction of silicon-based anode active materials.

[0004] Patent Document 1: International Publication No. 2021 / 095883 Summary of the Invention

[0005] Patent Document 1 discloses a current collector for lithium-ion batteries, which has a surface layer with a specific uneven structure on the surface in contact with the active material layer (claim 1). Preferably, this current collector has a surface layer with a mesh structure on a resin current collector substrate (claim 8). More preferably, the mesh structure constituting the surface layer is embedded in the resin current collector substrate (section 0088). A metal current collector substrate can be used instead of the resin current collector substrate (section 0092).

[0006] When the current collector of Patent Document 1 is applied to a bipolar electrode sheet using silicon-based negative electrode active material, the surface layer with an uneven structure moves in conjunction with the expansion of the negative electrode active material layer during charging. The movement of the surface layer can cause damage to the current collector substrate, potentially resulting in a short circuit between the positive and negative electrodes.

[0007] The present invention was made in view of the above circumstances, and its object is to provide a bipolar battery that can suppress the current collector damage when the negative electrode active material layer expands during charging, even when using silicon-based negative electrode active materials, and can suppress short circuits between the positive and negative electrodes.

[0008] The bipolar battery of the present invention comprises a bipolar electrode sheet and a non-aqueous electrolyte, wherein the bipolar electrode sheet comprises: a negative current collector having a second metal foil having one or more through holes laminated on the surface of a first metal foil without through holes via an adhesive layer comprising a thermoplastic resin; a negative active material layer formed on the surface of the second metal foil and comprising a silicon-based negative active material; a positive current collector laminated on the back side of the first metal foil and composed of a third metal foil; and a positive active material layer formed on the back side of the positive current collector, wherein the adhesive layer comprises: a first adhesive portion existing between the surface of the first metal foil and the back side of the second metal foil; and a second adhesive portion existing within the one or more through holes of the second metal foil.

[0009] In the above-mentioned bipolar electrode sheet, the negative current collector has a structure in which a second metal foil having one or more through holes is laminated on the surface of a first metal foil without through holes via an adhesive layer containing thermoplastic resin.

[0010] The adhesive layer possesses appropriate flexibility to mitigate stress. It can swell and soften with the electrolyte. When the negative electrode active material layer containing the silicon-based negative electrode active material expands during charging, the adhesive layer can alleviate its stress, suppressing the increase in the area of ​​the first and second metal foils and the resulting damage to the negative electrode current collector. Furthermore, the presence of a first metal foil without through holes between the second metal foil and the positive electrode current collector effectively suppresses the transmission of the effects of the expansion of the negative electrode active material layer containing the silicon-based negative electrode active material during charging to the positive electrode current collector.

[0011] In the bipolar battery of the present invention, the above-mentioned effects interact with each other, and even if the negative electrode active material layer containing silicon-based negative electrode active material expands during charging, it can effectively suppress the damage of the negative electrode current collector and the positive electrode current collector, and can effectively suppress the short circuit between the positive and negative electrodes.

[0012] Invention Effects

[0013] According to the present invention, a bipolar battery is provided that can suppress the current collector damage when the negative electrode active material layer expands during charging, even when using silicon-based negative electrode active materials, and can suppress short circuits between the positive and negative electrodes. Attached Figure Description

[0014] Figure 1 This is a schematic overall view showing a structural example of a bipolar battery according to one embodiment of the present invention.

[0015] Figure 2 This is an exploded schematic cross-sectional view of an electrode stack according to one embodiment of the present invention.

[0016] Figure 3 This is a schematic cross-sectional view of a bipolar electrode sheet according to one embodiment of the present invention.

[0017] Figure 4 This is an example of a schematic plan view of the second metal foil.

[0018] Figure 5 This is a table showing the main manufacturing conditions and evaluation results for each of Examples E1 to E8.

[0019] Figure 6 This is a table showing the main manufacturing conditions and evaluation results for each of the comparative examples EC1 and EC2. Detailed Implementation

[0020] Bipolar battery

[0021] The structure of a bipolar battery according to one embodiment of the present invention will be described with reference to the accompanying drawings.

[0022] exist Figure 2 and Figure 3 In the stacked structure shown, the upper side is the surface side, and the lower side is the back side. Furthermore, the designations of surface and back side in this specification are for convenience only and do not limit their actual positional relationship in use.

[0023] like Figure 1 As shown, the bipolar battery 1 contains an electrode stack 2 and a non-aqueous electrolyte (symbols omitted) within the battery container 3.

[0024] like Figure 2 As shown, the electrode stack 2 is a stack consisting of a positive electrode ES1 with a positive active material layer PE formed on the back side of the positive current collector C1, one or more bipolar electrode ES2 with a negative active material layer NE formed on the surface of the current collector C2 and a positive active material layer PE formed on the back side of the current collector C2, and a negative electrode ES3 with a negative active material layer NE formed on the surface of the negative current collector C3, which are stacked via a separator SP.

[0025] In the electrode stack 2, the positive electrode active material layer PE and the negative electrode active material layer NE are alternately arranged. A separator SP is disposed between adjacent positive electrode plates ES1 and bipolar electrode plates ES2. A separator SP is disposed between adjacent bipolar electrode plates ES2 and negative electrode plates ES3. When the electrode stack 2 includes multiple bipolar electrode plates ES2, a separator SP is disposed between adjacent bipolar electrode plates ES2.

[0026] like Figure 3As shown, the bipolar electrode sheet ES2 has: a negative current collector 10, on the surface 11A of a first metal foil 11 without through holes, a second metal foil 12 having one or more through holes 12H is laminated thereon via an adhesive layer 13 containing thermoplastic resin; a negative active material layer 20, formed on the surface 12A of the second metal foil 12, and containing a silicon-based negative active material; a positive current collector 30, laminated on the back side 11B of the first metal foil 11 and composed of a third metal foil; and a positive active material layer 40, formed on the back side 30B of the positive current collector 30.

[0027] Examples of metals constituting the first metal foil 11 and the second metal foil 12 include copper and copper alloys. The first metal foil 11 and the second metal foil 12 are preferably copper foils.

[0028] The thickness of the first metal foil 11 is preferably 1 μm or more and 30 μm or less. The lower limit is more preferably 2 μm, further preferably 3 μm, further preferably 5 μm, further preferably 7 μm, particularly preferably 8 μm, and most preferably 10 μm. The upper limit is more preferably 28 μm, further preferably 25 μm, further preferably 23 μm, further preferably 20 μm, particularly preferably 18 μm, and most preferably 15 μm.

[0029] By having a first metal foil 11 without through holes of appropriate thickness between the second metal foil 12 and the positive current collector 30, the effect of the expansion of the negative electrode active material layer 20 containing silicon-based negative electrode active material during charging can be effectively suppressed from affecting the positive current collector 30.

[0030] A second metal foil 12 having one or more through holes 12H can be manufactured by forming one or more through holes 12H on a metal foil that does not have through holes using known methods such as laser processing.

[0031] The thickness of the second metal foil 12 is preferably 1 μm or more and 30 μm or less. The lower limit is more preferably 2 μm, further preferably 3 μm, further preferably 5 μm, further preferably 7 μm, particularly preferably 8 μm, and most preferably 10 μm. The upper limit is more preferably 28 μm, further preferably 25 μm, further preferably 23 μm, further preferably 20 μm, particularly preferably 18 μm, and most preferably 15 μm.

[0032] If the thickness of the second metal foil 12 is above the aforementioned lower limit, the stress mitigation effect based on the adhesive layer 13 containing thermoplastic resin can be effectively obtained, and short circuits between the positive and negative electrodes can be effectively suppressed. If the thickness of the second metal foil 12 is below the aforementioned upper limit, the material cost of the negative electrode current collector 10 can be suppressed.

[0033] From the viewpoint of ease of formation, the planar shape of the through hole 12H formed in the second metal foil 12 is preferably circular or elliptical, and more preferably circular.

[0034] like Figure 4 As shown, the second metal foil 12 preferably has a structure in which multiple through holes 12H are arranged in a regular pattern (e.g., a matrix pattern) when viewed from above.

[0035] The diameter D of the through hole 12H is preferably 10 μm or more and 300 μm or less. The lower limit is more preferably 20 μm, further preferably 30 μm, further preferably 40 μm, further preferably 50 μm, particularly preferably 60 μm, and most preferably 70 μm. The upper limit is more preferably 280 μm, further preferably 250 μm, further preferably 230 μm, further preferably 200 μm, further preferably 180 μm, further preferably 150 μm, particularly preferably 130 μm, and most preferably 100 μm.

[0036] Unless otherwise specified, the diameter of the through hole in this specification is the maximum diameter of the through hole.

[0037] The spacing S between adjacent through holes 12H is preferably 1 μm or more and 100 μm or less. The lower limit is more preferably 2 μm, further preferably 3 μm, further preferably 4 μm, further preferably 5 μm, further preferably 6 μm, further preferably 7 μm, particularly preferably 8 μm, and most preferably 10 μm. The upper limit is more preferably 90 μm, further preferably 80 μm, further preferably 70 μm, further preferably 60 μm, further preferably 50 μm, further preferably 40 μm, particularly preferably 30 μm, and most preferably 20 μm.

[0038] In the second metal foil 12, the ratio (also called the opening area ratio) of the total area of ​​one or more through holes 12H to the total area of ​​the metal portion 12M and one or more through holes 12H is preferably 10% or more and 90% or less. The lower limit is more preferably 15%, further preferably 20%, further preferably 25%, further preferably 30%, further preferably 35%, further preferably 40%, further preferably 45%, further preferably 50%, particularly preferably 55%, and most preferably 60%. The upper limit is more preferably 85%, further preferably 80%, further preferably 75%, particularly preferably 70%, and most preferably 65%.

[0039] If the opening area ratio is above the lower limit mentioned above, the stress relief effect based on the adhesive layer 13 containing thermoplastic resin can be effectively obtained, and the short circuit between the positive and negative electrodes can be effectively suppressed.

[0040] If the opening area ratio is below the above-mentioned upper limit, the increase in resistance caused by the adhesive layer 13 containing thermoplastic resin can be suppressed, and the decrease in capacity retention due to uneven reactions such as lithium deposition during cyclic charging and discharging can be suppressed.

[0041] Examples of thermoplastic resins included in the adhesive layer 13 include olefin resins such as polyethylene and polypropylene; (meth)acrylic resins such as polymethyl methacrylate (PMMA); styrene resins such as methyl methacrylate-styrene copolymer (MS resin), acrylonitrile-styrene copolymer (AS resin), styrene-maleic anhydride copolymer (SMA resin), and styrene-maleic anhydride-methyl methacrylate copolymer (SMM resin); ester resins such as polyethylene terephthalate and polybutylene terephthalate; amide resins such as nylon 6 and nylon 66; carbonate resins such as polycarbonate; urethane resins such as polyurethane; and halogen-containing resins such as polyvinyl chloride, polyvinylidene chloride, and polyvinylidene fluoride (PVDF). From the viewpoint of chemical stability and heat resistance, halogen-containing resins such as polyvinyl chloride, polyvinylidene chloride, and polyvinylidene fluoride (PVDF) are preferred, and polyvinylidene fluoride (PVDF) is more preferred.

[0042] The adhesive layer 13 may also contain one or more conductive agents such as acetylene black, as needed.

[0043] The content of thermoplastic resin in the adhesive layer 13 (total amount when there are multiple types) is preferably 90% by mass or more and 100% by mass or less. The lower limit is more preferably 95% by mass.

[0044] The adhesive layer 13 includes a first adhesive portion 13X existing between the surface 11A of the first metal foil 11 and the back surface 12B of the second metal foil 12, and a second adhesive portion 13Y existing in one or more through holes 12H of the second metal foil 12.

[0045] The thickness of the first adhesive portion 13X is preferably 1 μm or more and 20 μm or less. The lower limit is more preferably 2 μm, and particularly preferably 3 μm. The upper limit is more preferably 18 μm, further preferably 15 μm, further preferably 12 μm, further preferably 10 μm, further preferably 8 μm, further preferably 7 μm, further preferably 6 μm, particularly preferably 5 μm, and most preferably 4 μm.

[0046] If the thickness of the first adhesive portion 13X is above or above the aforementioned lower limit, the stress mitigation effect based on the adhesive layer 13 containing thermoplastic resin can be effectively obtained, and short circuits between the positive and negative electrodes can be effectively suppressed. If the thickness of the first adhesive portion 13X is below or below the aforementioned upper limit, the increase in resistance caused by the adhesive layer 13 containing thermoplastic resin is suppressed, and the decrease in capacity retention due to uneven reactions such as lithium deposition during cyclic charging and discharging can be suppressed.

[0047] The adhesive layer 13 can be formed, for example, by overlapping a second copper foil 12 onto a first copper foil 11, coating it with a solution obtained by dissolving a thermoplastic resin such as polyvinylidene fluoride (PVDF) in a known solvent such as N-methyl-2-pyrrolidone (NMP), and then drying to remove the solvent. Examples of methods for drying to remove the solvent include heating, vacuum drying, and vacuum heating.

[0048] Examples of metals constituting the positive current collector 30 (third metal foil) include aluminum and aluminum alloys. The positive current collector 30 (third metal foil) is preferably aluminum foil.

[0049] The negative current collector 10 and the positive current collector 30 can be bonded together as needed via a known adhesive layer (not shown). The adhesive layer bonding the negative current collector 10 and the positive current collector 30 preferably contains a thermoplastic resin such as polyvinylidene fluoride (PVDF), and may further contain a conductive agent such as acetylene black as needed.

[0050] In the bipolar electrode sheet ES2 of this embodiment, the negative current collector 10 has a structure in which a second metal foil 12 having one or more through holes 12H is laminated on the surface 11A of a first metal foil 11 without through holes via an adhesive layer 13 containing a thermoplastic resin such as polyvinylidene fluoride (PVDF).

[0051] The adhesive layer 13 has appropriate flexibility to mitigate stress. The adhesive layer 13 can swell and soften with the electrolyte. When the negative electrode active material layer 20, containing silicon-based negative electrode active material, expands during charging, the adhesive layer 13 can mitigate its stress, suppressing the increase in the area of ​​the first metal foil 11 and the second metal foil 12 and the resulting damage to the negative electrode current collector 10. Furthermore, the presence of a first metal foil 11 without through holes between the second metal foil 12 and the positive electrode current collector 30 effectively suppresses the impact of the expansion of the negative electrode active material layer 20 containing silicon-based negative electrode active material during charging on the positive electrode current collector 30.

[0052] In the bipolar battery 1 of this embodiment, the above-mentioned effects interact with each other, and even when the negative electrode active material layer 20 containing silicon-based negative electrode active material expands during charging, the damage to the negative electrode current collector 10 and the positive electrode current collector 30 can be effectively suppressed, and the short circuit between the positive and negative electrodes can be effectively suppressed.

[0053] Examples of bipolar batteries include lithium-ion rechargeable batteries.

[0054] The following section uses lithium-ion secondary batteries as an example to explain the main components.

[0055] (Positive electrode active material layer)

[0056] Examples of positive electrode active materials include LiCoO2, LiMnO2, LiMn2O4, LiNiO2, and LiNi. x Co (1-x) O2 and LiNi x Co y Mn (1-x-y) O2 and other lithium-containing composite oxides, etc. (where 0 < x < 1, 0 < y < 1).

[0057] The positive electrode active material layer can be formed by coating an electrode mixture containing positive electrode active material and dispersion medium onto the positive electrode current collector, followed by heating, drying, and stamping.

[0058] (Negative electrode active material layer)

[0059] The negative electrode active material includes one or more silicon-based negative electrode active materials. Examples of silicon-based negative electrode active materials include silicon monoxide.

[0060] The negative electrode active material can also include one or more non-silicon-based negative electrode active materials as needed. Examples of non-silicon-based negative electrode active materials include carbon such as graphite, metallic lithium, lithium alloys, and transition metal oxides / transition metal nitrides / transition metal sulfides that can be doped / dedoped with lithium ions.

[0061] The content of silicon-based negative electrode active material in the negative electrode active material layer is preferably 1% by mass or more and 100% by mass or less. From the viewpoint of increasing the capacity of bipolar batteries, the lower limit is more preferably 2% by mass, further preferably 5% by mass, even more preferably 10% by mass, particularly preferably 15% by mass, and most preferably 20% by mass. From the viewpoint of suppressing the expansion of the negative electrode active material layer during charging, the upper limit is more preferably 90% by mass, further preferably 80% by mass, even more preferably 70% by mass, even more preferably 60% by mass, even more preferably 50% by mass, particularly preferably 40% by mass, and most preferably 30% by mass.

[0062] The negative electrode active material layer can be formed by coating an electrode mixture containing negative electrode active material and dispersion medium onto the negative electrode current collector, followed by heating, drying, and stamping.

[0063] (Non-aqueous electrolyte)

[0064] As a non-aqueous electrolyte, a non-aqueous electrolyte containing lithium electrolyte is preferably dissolved in a mixed solvent of high dielectric constant carbonate solvents such as propylene carbonate and ethylene carbonate and low viscosity carbonate solvents such as diethyl carbonate, methyl ethyl carbonate and dimethyl carbonate.

[0065] As a mixed solvent, for example, a mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) / dimethyl carbonate (DMC) and a mixed solvent of ethylene carbonate (EC) / fluoroethylene carbonate (FEC) / ethyl methyl carbonate (EMC) / dimethyl carbonate (DMC) are preferred.

[0066] Examples of lithium-containing electrolytes include LiPF6, LiBF4, LiClO4, LiAsF6, Li2SiF6, and LiiOSO2C. k F (2k+1)( (k = integers from 1 to 8), and LiPF n {C k F (2k+1)} (6-n)( Lithium salts and their combinations thereof, including integers n=1 to 5 and k=1 to 8.

[0067] (Diaphragm)

[0068] As a separator, porous membranes made of polyolefins are preferred, such as porous membranes made of PP (polypropylene), porous membranes made of PE (polyethylene), and porous membranes made of PP (polypropylene)-PE (polyethylene) laminates.

[0069] (Battery container)

[0070] As a battery container, a known battery container can be used.

[0071] Example

[0072] The following describes the embodiments and comparative examples related to the present invention.

[0073] [Examples E1-E8]

[0074] (The production of positive electrode sheets)

[0075] The positive electrode active material (LiNi) 0.8 Co 0.1 Mn 0.1 A paste-like positive electrode mixture (solid content: 65% by mass) was prepared by mixing 93 parts by mass of O2 (average particle size: 10 μm), 4 parts by mass of conductive agent (granular acetylene black), 3 parts by mass of binder (polyvinylidene fluoride (PVDF)), and an appropriate amount of N-methyl-2-pyrrolidone (NMP).

[0076] As the positive current collector, a 30μm thick aluminum foil was prepared. The obtained positive electrode additive was coated onto the back side of this foil using a comma coater (registered trademark). The foil was then heated and dried at 120°C for 30 minutes, followed by stamping to form the positive electrode active material layer (drying weight per unit area: 20mg / cm²). 2Density after stamping: 2.7 g / cc. The thickness of the coated film was adjusted by the roller gap of the comma coating machine (registered trademark).

[0077] The obtained positive electrode sheet is cut and processed into a rectangular shape of 15cm×8cm. The positive electrode active material layer within a range of 2cm from the outer perimeter is further peeled off to expose the aluminum foil in this part.

[0078] (Fabrication of the negative current collector)

[0079] As the first metal foil, a 10μm thick copper foil without through holes (non-porous copper foil) was prepared.

[0080] As the second copper foil, it is prepared by laser processing such as Figure 4 The image shows a perforated copper foil with multiple through holes regularly arranged in a matrix at equal intervals on approximately the entire surface.

[0081] A second copper foil (perforated) was overlapped on top of a first copper foil (non-perforated). A solution (5% by mass) of polyvinylidene fluoride (PVDF) dissolved in N-methyl-2-pyrrolidone (NMP) was then coated onto the first copper foil (non-perforated). The coating was then dried under reduced pressure at 120°C for 30 minutes. The thickness of the coating film was adjusted by controlling the gap between the bar of the bar coater and the material being coated. This yielded the desired result. Figure 3 The negative current collector shown is composed of a first copper foil (non-porous copper foil), a polyvinylidene fluoride (PVDF) adhesive layer, and a second copper foil (porous copper foil).

[0082] In embodiments E1 to E8, changes were made. Figure 5 A negative current collector was obtained by meeting one or more of the conditions shown.

[0083] (Making of negative electrode plates)

[0084] A paste-like negative electrode compound (solid content: 65% by mass) was prepared by mixing 68 parts by mass of spheroidized natural graphite (average particle size: 17 μm), 28 parts by mass of silica microparticles (average particle size: 6 μm), 0.5 parts by mass of carboxymethyl cellulose (CMC), 2 parts by mass of styrene-butadiene rubber, 1.2 parts by mass of lithium polyacrylate, 0.3 parts by mass of carbon nanotubes (CNTs), and 85 parts by mass of ion-exchanged water.

[0085] The obtained negative electrode mixture was coated onto the surface of the perforated copper foil side of the aforementioned negative electrode current collector using a comma coating machine (registered trademark). The mixture was then heated and dried at 120°C for 30 minutes, followed by stamping to form a negative electrode active material layer (drying weight per unit area: 5 mg / cm²). 2 Density after stamping: 1.2 g / cc. The thickness of the coated film was adjusted by the roller gap of the comma coating machine (registered trademark).

[0086] The obtained negative electrode sheet is cut and processed into a rectangle of 15cm×8cm. The negative electrode active material layer within a range of 2cm from the outer perimeter is further peeled off to expose the copper foil in this part.

[0087] (Fabrication of bipolar electrode sheets)

[0088] A bonding slurry was prepared by mixing 10 parts by weight of acetylene black, 5 parts by weight of polyvinylidene fluoride (PVDF), and 15 parts by weight of N-methyl-2-pyrrolidone (NMP).

[0089] Next, the above-mentioned positive electrode sheet and the above-mentioned negative electrode sheet are laminated with the obtained adhesive slurry to form a positive current collector and a negative current collector facing each other, and then heated and dried at 120°C for 30 minutes to obtain a bipolar electrode sheet with a laminated structure of negative electrode sheet / adhesive layer / positive electrode sheet.

[0090] The adhesive slurry is applied using a scraper coater, and the thickness of the coating film is adjusted by the gap between the scraper of the scraper coater and the material being coated.

[0091] (Fabrication of electrode stacks)

[0092] As a sealing slurry, a mixed slurry of 7 parts by weight of polyvinylidene fluoride (PVDF) and 93 parts by weight of N-methyl-2-pyrrolidone (NMP) was prepared.

[0093] As a diaphragm, a porous polyethylene (PE) diaphragm with a thickness of 11.5cm×11.5cm and 20μm was prepared.

[0094] As an intermediate film, a 15cm×3cm, 30μm thick polyimide tape was prepared, which was bent along a central axis parallel to the long side.

[0095] like Figure 2 As shown, as electrode sheets, one positive electrode sheet, multiple bipolar electrode sheets and one negative electrode sheet are prepared, and these electrode sheets are stacked by a separator to obtain an electrode stack.

[0096] The following processes were performed: stacking of a negative electrode sheet as the lower electrode sheet and a bipolar electrode sheet as the upper electrode sheet; stacking of a bipolar electrode sheet as the lower electrode sheet and a bipolar electrode sheet as the upper electrode sheet; and stacking of a bipolar electrode sheet as the lower electrode sheet and a positive electrode sheet as the upper electrode sheet.

[0097] The exposed copper foil at the periphery of the lower electrode plate and the exposed aluminum foil at the periphery of the upper electrode plate are overlapped with the aforementioned sealing slurry (hand-applied) and then heated and dried at 120°C for 30 minutes to form a sealing material. The unit area weight of the sealing material is set to 0.5 mg / cm². 2Above and 1.0 mg / cm 2 the following.

[0098] In addition, during the above-mentioned lamination, the intermediate film (two in total) was sandwiched between the long sides of the lower electrode sheet and the long sides of the upper electrode sheet, which are opposite each other. At this time, the intermediate film was arranged in such a way that the bent portion of the intermediate film was located on the inside and the 1 cm wide portion of the outer side of the intermediate film was in contact with the sealing material and fixed thereto.

[0099] Repeating the above stacking process, an electrode stack with a combination (N) of "9" positive and negative active material layers was obtained. Additionally, an unsealed portion of approximately 1 cm width was left on one short side of the electrode stack as an electrolyte injection port.

[0100] (Battery manufacturing)

[0101] As a non-aqueous electrolyte, a solution containing 1 mol / kg of LiPF6 was prepared in a mixed solvent of ethylene carbonate (EC) / vinyl fluorocarbon (FEC) / ethyl methyl carbonate (EMC) / dimethyl carbonate (DMC) (volume ratio 0.268 / 0.032 / 0.3 / 0.4).

[0102] Under reduced pressure, 1.5 ml of the non-aqueous electrolyte was injected into the electrode stack through the electrolyte injection port, and then the electrolyte injection port was sealed using the sealing slurry and a known method.

[0103] Finally, aluminum tabs and copper tabs were ultrasonically welded onto the outermost aluminum foil current collector and the outermost copper foil current collector, respectively, to obtain a lithium-ion secondary battery.

[0104] [Comparative Example EC1]

[0105] As the negative electrode current collector, only the first copper foil (a 10 μm thick copper foil without through holes) (a non-porous copper foil) was used. Otherwise, a lithium-ion secondary battery was obtained in the same manner as in Examples E1 to E8.

[0106] [Comparative Example EC2]

[0107] As the first copper foil, two 10μm thick copper foils without through holes (non-perforated copper foils) were prepared.

[0108] Two first copper foils (non-porous copper foils) were laminated using a solution (5% by mass) of polyvinylidene fluoride (PVDF) dissolved in N-methyl-2-pyrrolidone (NMP), and then dried under reduced pressure at 120°C for 30 minutes. This yielded a negative electrode current collector consisting of a first copper foil (non-porous copper foil), a PVDF adhesive layer (3 μm thick), and another first copper foil (non-porous copper foil). Using the obtained negative electrode current collector, a lithium-ion secondary battery was obtained in the same manner as in Examples E1 to E8.

[0109] [Evaluation of Battery Characteristics]

[0110] Regarding the lithium-ion secondary batteries obtained in each example, after the initial charge-discharge under the following conditions, cyclic charge-discharge tests were conducted under the following conditions. Furthermore, constant current / constant voltage charging (CCCV) was used as the charging method, and constant current / constant voltage discharging was used as the discharging method.

[0111] <Initial Charge and Discharge>

[0112] Charging: 4.2V×N, 3mA cutoff, current rate: 60mA

[0113] Discharge: 2.5V×N, 3mA cutoff, current value: 60mA.

[0114] <Cyclic Charge-Discharge Test>

[0115] Charging: 4.2V×N, 15mA cutoff, current rate: 300mA

[0116] Discharge: 2.5V×N, 15mA cutoff, Current: 300mA

[0117] Number of cycles: 100.

[0118] Here, N is the number of combinations of positive and negative active material layers contained in the electrode stack (specifically, "9").

[0119] For samples that short-circuited before 100 charge-discharge cycles, the time of the short circuit [number of cycles] was recorded (in which cycle the short circuit occurred). For samples that could undergo 100 charge-discharge cycles, the time of the short circuit [number of cycles] was recorded as ">100".

[0120] <Capacity retention rate after 50 charge-discharge cycles>

[0121] For samples that can undergo 50 charge-discharge cycles without short circuits, the capacity retention rate [%) was calculated according to the following formula.

[0122] [Capacity retention rate (%)] = [Discharge capacity at 50th cycle] / [Discharge capacity at 1st cycle] × 100

[0123] <Electrode size changes>

[0124] For samples that can undergo 100 charge-discharge cycles without short circuits, after the 100 charge-discharge cycles are completed, the battery is disassembled, the maximum length of the short side of the electrode is measured, and the dimensional change of the electrode (the dimensional change from the initial value (=8cm)) [mm] is calculated according to the following formula.

[0125] [Electrode dimensional change (mm)] = [Maximum length of the shorter side of the electrode after 100 charge-discharge cycles (mm)] - [Initial length of the shorter side of the electrode (mm)]

[0126] For samples that were short-circuited before 100 charge-discharge cycles, the dimensional changes of the electrodes were measured using the same method at the point when the short circuit occurred.

[0127] [Summary of Results]

[0128] For each of Examples E1 to E8 and Comparative Examples EC1 and EC2, the main manufacturing conditions and evaluation results are shown below. Figure 5 , Figure 6 In these diagrams, conditions not explicitly stated are designated as common conditions.

[0129] In comparative examples EC1 and EC2, the electrode size increased with fewer charge-discharge cycles, and a short circuit occurred between the positive and negative electrodes.

[0130] In contrast, in Examples E1 to E8, the stress caused by the expansion of the negative electrode active material layer can be sufficiently mitigated, and the dimensional changes of the electrode and the resulting short circuit between the positive and negative electrodes can be suppressed. Among them, excellent results were obtained in Examples E1 to E4, E6, E8, and especially Examples E1 to E4, in which the thickness-to-opening area ratio of the second metal foil and the thickness of the first adhesive portion were preferably designed.

[0131] This invention is not limited to the above-described embodiments and examples. As long as the spirit of this invention is not departed, appropriate design changes can be made.

[0132] Symbol Explanation

[0133] 1-Bipolar battery, 10-Negative current collector, 11-First metal foil, 11A-Surface, 11B-Back side, 12-Second metal foil, 12A-Surface, 12B-Back side, 12H-Through hole, 12M-Metal part, 13-Adhesive layer, 13X-First adhesive part, 13Y-Second adhesive part, 20-Negative active material layer, 30-Positive current collector, 30B-Back side, 40-Positive active material layer, ES2-Bipolar electrode sheet.

Claims

1. A bipolar battery comprising bipolar electrode plates and a non-aqueous electrolyte, characterized in that, The bipolar electrode sheet has the following characteristics: A negative current collector has a second metal foil having one or more through holes laminated on the surface of a first metal foil without through holes via an adhesive layer containing thermoplastic resin. A negative electrode active material layer is formed on the surface of the second metal foil and contains a silicon-based negative electrode active material; A positive current collector, which is stacked on the back side of the first metal foil and is composed of a third metal foil; and A positive electrode active material layer is formed on the back side of the positive electrode current collector. The adhesive layer includes: a first adhesive portion existing between the surface of the first metal foil and the back surface of the second metal foil; and a second adhesive portion existing within the one or more through holes of the second metal foil.

2. The bipolar battery according to claim 1, characterized in that, The thickness of the second metal foil is more than 1 μm and less than 30 μm. In the second metal foil, the ratio of the total area of ​​the one or more through holes to the total area of ​​the metal portion and the one or more through holes is 10% or more and 90% or less.

3. The bipolar battery according to claim 1 or 2, characterized in that, The thickness of the first adhesive portion is more than 1 μm and less than 20 μm.

4. The bipolar battery according to claim 1 or 2, characterized in that, The first metal foil and the second metal foil are copper foils. The third metal foil is aluminum foil. The thermoplastic resin includes polyvinylidene fluoride.

5. The bipolar battery according to claim 1 or 2, characterized in that, The second metal foil has a structure in which multiple through holes are arranged in a regular pattern when viewed from above.

Citation Information

Patent Citations

  • Lithium ion battery collector, production method for lithium ion battery collector, and lithium ion battery electrode

    WO2021095883A1